Strategies and Challenges of Implementing the Merdeka Curriculum in Senior High Schools - Setyaningsih, Rini; Mulyani, Sri; Irawati, Irawati; Kuswanti, Adlia; Ismaeil, Nadiah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The Merdeka Curriculum aims to promote differentiated learning practices in line with the diverse backgrounds of students in Indonesia. However, its implementation at the secondary school level still faces various challenges. This study aims to analyze the strategies and barriers encountered in the implementation of this curriculum. Using a qualitative descriptive method, data were collected through semi-structured in-depth interviews with curriculum managers, supported by direct observation in the learning environment. Data analysis was conducted thematically, following the procedures of Braun and Clarke. The results revealed three main findings: the limited competencies of teachers in applying differentiated learning principles, disparities in access to digital learning resources, and low student involvement in the design of learning activities, which collectively hinder the effectiveness of the curriculum. These findings indicate that national curriculum reform cannot solely rely on policy design but requires strengthening context-based capacities at the educational unit level to realize the full potential of curriculum transformation effectively.